Unique SNP in CD44 Intron 1 and its Role in Breast Cancer Development - Zhou, Juhua (2010)
In the current study, we investigated if CD44 polymorphisms are associated with increased susceptibility to breast cancer. Direct nucleotide sequencing analysis identified a novel and unique single nucleotide polymorphism (SNP, designated as CD44 Ex2+14 A>G) in the CD44 intron 1 region in 84% of breast cancer patients, which was significantly higher than that seen in normal donors. Moreover, the breast cancer patients with homozygous unique SNP in CD44 intron 1 had breast cancer at earlier ages, larger tumor burden, more regional lymph node metastases at the time of diagnosis, and higher cancer recurrence rate. There was a strong association between the unique SNP in CD44 intron 1 and CD44 expression on peripheral blood mononuclear cells. Our results suggest that CD44 polymorphism is associated with breast cancer development, and CD44 polymorphism analysis may be effectively used in the risk assessment, prediction, prevention, diagnosis and genetic epidemiological analysis of breast cancer.